1996
DOI: 10.1111/j.1472-765x.1996.tb01194.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivacin 140, a novel bacteriocin from Lactobacillus salivarius subsp. salicinius T140 active against pathogenic bacteria

Abstract: Fifteen of 353 environmental isolates of lactic acid bacteria consistently showed activity against Listeria monocytogenes, Streptococcus mutans, Actinomyces viscosus, and/or Propionibacterium acnes. Strain T140, isolated from the surface of Japanese pampas grass leaves and identified as Lactobacillus salivarius subsp. salicinius, also had activity against several Lactobacillus species, Staphylococcus aureus and Yersinia enterocolitica. Since the antagonistic factor(s) produced by T140 was sensitive to a proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…1998). Some LAB produce bacteriocins which are proteinaceous substances with antimicrobial activity (Arihara et al . 1996; van Reenen et al .…”
Section: Discussionmentioning
confidence: 99%
“…1998). Some LAB produce bacteriocins which are proteinaceous substances with antimicrobial activity (Arihara et al . 1996; van Reenen et al .…”
Section: Discussionmentioning
confidence: 99%
“…The production of bacteriocin or bacteriocin-like substances has been shown in some strains of L. salivarius samples taken from grass leaves [Arihara et al, 1996], human vaginas [Juarez Tomas et al, 2002] as well as in animals [Robredo and Torres, 2000] and these were found to have inhibitory or bactericidal actions against various bacteria, including S. mutans [Arihara et al, 1996]. In the present study, superinfection with L. salivarius LS1952R did not reduce or inhibit the establishment of S. mutans MT8148R in the oral cavity of rats.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, intensive research over the last 20 years has identified several novel bacteriocins, many of which are produced by intestinal and/or probiotic bacteria (13). The production of bacteriocins by Lactobacillus salivarius strains has been reported previously (1,12,14,17), and ABP-118, a twocomponent class II bacteriocin produced by a human intestinal probiotic strain, L. salivarius subsp. salivarius UCC118, has been fully characterized at the molecular level (6).…”
mentioning
confidence: 99%